Pengaruh Intellectual Capital Terhadap Stock Return dengan Mediasi Return On Assets - Arcelia Angelica Soputra; Adwin Surja Atmadja (Business Accounting Review, 2017)
Today’s economic-based is undergoing a transition from industrial era to a knowledged-based economy, where knowledge becomes an important factor that can differentiate firm’s ability to create competitive advantages. IC itself is defined as existing knowledge on employees who become a key resources for the company’s. However previous research on the impact of IC to stock return is still inconsistent. The purpose of this study to examine the impact of IC to stock return with financial performance as mediation variable. IC will be measured by Pulic’s VAIC, cummulative abnormal return for stock return measurement, and ROA to measure financial performance. It also used firm size and debt to equity ratio as a control variables. This reasearch use company in LQ45 period 2010 until 2015 with 108 observations.The results showed there is no significant correlation between IC and stock return, but however has positive significant affect on ROA. The results also showed that firm size didn’t have affect on financial performance and stock return, and also debt to equity ratio had no significant affect on firm performance and stock return.